Job stress, what are the dimension involved case study: MASkargo / Faizura Zahari - Zahari, Faizura (Faculty of Business and Management, 2010)
Job life is one of the important parts of our daily lives which cause a great deal of stress. Due to the competitive nature of the job environment most of the people in the world are spending their time for job related work purposes resulting ignore the stressor those are influencing their work and life. Stress as an occupational illness can have organizational effects with workers showing higher propensity to leave their jobs, higher rates of absenteeism, and increased tensions in the workplace. However, the most important negative effects may well be those that affect productivity and employee health Present research study on five factors or dimension involved that could be the tools that can stress among the employees which are role conflict, relationship with others, homework interface, role ambiguity and performance pressure.